Position change strategies in the current global value chains: a micro-level aspect - I. P. Komarova; E. S. Novikova (Вестник университета)
The study includes an analysis of various levels of strategies for changing the positions of companies in the existing global value creation chains. First of all, companies in the technology sector of the economy in the Asian region, including companies of South Korea and China, have been considered. As the result of the research, some factors influencing the change in the subordinate position of companies in global value creation chains, -have been presented. In addition, the impact of these factors on changing positions of companies in the high-tech sector in global value creation chains has been analysed. The most frequently repeated factors have been structured and presented as a table.